Ruler's Dues Comon Teachings of Ahl-e-Kitab and Islam - Usman Shafiq; Dr. Mahmood Ahmad (jihat-ul-islam, 2024)
A happy and strong relationship between the ruler and public is the foundation of a developed state and stable society. One of the majior challenges facing the state in the present era is political instability. The reason for this is that ruler is neglecting his duties and ignoring the rights of his citizens. If a ruler fulfills his obligations in a proper manner, this tension can be eliminated to a large extent. Pakistan is an Islamic state, Muslims are the majority here and the religious trend is found to a considerable extent. So, in this context, by daring to research a part of this broad subject, we have tried to prove that not only Islam, but also the previous heavenly books have valuable teachings on this topic. Therefore, the common teachings of the People of the Book and Islam have been presented. So that the importance of this subject can be estimated and a ruler also be wel aware of his duties from a religious point of view so that he can be successful in this world and the hereafter.